Produção de carvão vegetal em cilindros metálicos verticais: alguns aspectos referentes à sustentabilidade - Santos, Sueli de Fátima de Oliveira Miranda (2007)
Brazil produces approximately one third of the world’s charcoal annual production, of which, around ninety percent are designated to the Brazilian production of pig-iron, iron-alloys, mainly (FeSi, FeCr, FeMn, FeMo), pure silicon, among others. Surely, seventy percent of the charcoal are still produced using the traditional handicraft way, the same way as it was a century ago, and almost half of firewood still derives from native forests. The pressure for ecologically-right, socially fair and economically feasible production, has driven the search for cleaner and more efficient technologies which can meet these requirements and contribute to change the present charcoal production situation in Brazil. Researching a metallic vertical cylinder industrial charcoal production unit, and a traditional handicraft unit, both located on the state of Paraná, this dissertation intends to show that the industrial production model can replace the traditional one. According to the sustainability pillars, this industrial model has shown the possibility of 25% of firewood saving, pointing to an economical feasibility, an ecologically-right, and socially fair process, under the Brazilian work legislation. Finally it was evidenced that crucial point of the process is to burn the dirt smoke generated during the wood carbonization, using the generated heat for pre-drying the firewood and getting a clean gas emission at the end.